Fabrication and Cytotoxicity Testing of Silver Nitrate Modified PETG Scaffolds for Bone Applications - Mishbak, Hussein; Daskalakis, Evangelos; Hassan, Mohamed (Trends in Sciences, 2026)
This study examines the surface modification of 3D printed polyethylene terephthalate glycol (PETG) scaffolds by a simple and reproducible coating method using silver nitrate (AgNO3) and the cytotoxicity of the modified scaffolds is assessed. The main aims of the study were characterization of the structural and morphological changes on the surface of the scaffold after the treatment, more precisely the thickness of the deposited silver coating, and assessment of the biological effect on the HBL100 normal cell lines. The chemical protocol for scaffold modification was a multi-step process including the preparation of silver nitrate solution, a necessary pre-treatment of PETG scaffold using a sodium hydroxide (NaOH) solution, immersion of scaffold in the AgNO3 solution, sonication and final drying process. Atomic Force Microscopy (AFM) analysis was performed to measure the thickness of the coating, finding a high dependence of the coating on the 3D printing angle of the scaffold. The PETG scaffold with 0°/45° had a coating thickness of about 566 nm, which was much thicker than coatings on scaffolds with 0°/60°/120° and 0°/90° printing laydown patterns. The cytotoxicity of the scaffolds was tested by the standard MTT assay. The results of the assay including mean absorbance, mean inhibition percentage and standard deviation showed no significant cytotoxic effect from the coated scaffolds with the mean inhibition percentages ranging from a minimal 0.74% to 10.91%. This study demonstrates a viable and biocompatible method to functionalize 3D-printed PETG scaffolds which could have significant implications for various applications including tissue engineering and medical devices where the need to both structural integrity and non-toxic surface properties is paramount. HIGHLIGHTS The laydown pattern of 3D printing has a substantial impact on the thickness of silver nitrate coating on PETG scaffolds, varying from 89 nm (0°/60°/120°) to 566 nm (0°/45°) that allows rational surface functionalization. It is demonstrated that NaOH pretreatment and AgNO3 immersion is a simple and reproducible chemical coating method for functionalization of 3D printed PETG scaffolds with antimicrobial capabilities without significant structural degradation. Silver-coated PETG scaffolds have shown great biocompatibility with normal HBL100 cell lines with low cytotoxicity (0.74% - 10.91% inhibition) for all different printing geometries. Characterization AFM The geometry-dependent surface morphology of 0°/45° scaffolds reveal thick and rough coatings with aggregation of nanoparticles whereas and 0°/90° scaffolds reveal thin and uniform coatings ideal towards mechanical stability. Multifunctional bone scaffolds by combining the mechanical properties of PETG with the antimicrobial activity of silver have promising potential for use in bone regeneration applications where infection is a common problem without any decline in cellular compatibility. GRAPHICAL ABSTRACT